Challenges and outcome of Wilms′ tumour management in a resource-constrained setting - Wilde J.C.H; Lameris W; van Hasselt E; Molyneux E; Heij H; Borgstein E (Wolters Kluwer Medknow Publications, 2010)
Background: To review the results of Wilms′ tumour patients in a tertiary referral hospital in a developing country and to find ways of improving long-term survival. Patients and Methods: Between January 1998 and May 2004, 40 patients with Wilms′ tumour (WT) were admitted to Queen Elizabeth Central Hospital. Their files were reviewed and general physical condition on admission, pre-operative investigations, management and outcome were noted. Results: The mean age of presentation was 4.2 years with an equal distribution between the sexes. The mean BMI was 15 kg/m2 and more than 80% of the patients were either mildly (PCV <33%) or severely anaemic (PCV <24%). All patients presented with abdominal distension. Half of them had additional complaints including abdominal pain, haematuria, dyspnoea, oedema and or weight loss. Thirty-nine out of the forty patients received pre-operative chemotherapy. Of the 36 patients that underwent surgery, 32 underwent total nephrectomy, one a partial nephrectomy, and in three the tumour was irresectable. There were no intra-operative tumour ruptures. Only 15% of the patients completed their post-operative course of chemotherapy. The 1-year survival lies between 25% and 53%. Fifteen of the 36 patients operated were known to have a recurrence. Conclusion: The patients presented in an advanced stage of the disease. Survival rates are disappointing and recurrence rates are high. Some improvement in outcome may be expected with the implementation of more aggressive treatment protocols but early diagnosis, completion of treatment regimens are needed. Pro-active follow-up is essential to measure outcome.